1999
DOI: 10.1007/pl00010699
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders in 8–9-year-old children based on a diagnostic interview with the parents

Abstract: Using three questionnaires, the Rutter Parent Questionnaire (RA2), The Rutter Teacher Questionnaire (RB2) and the Children's Depression Inventory (CDI), we screened 8-9-year-old children representing a total annual birth cohort (N = 60007) in Finland. In a second stage we interviewed the parents of 119 screen negative, and 316 screen positive children by using a structured parent interview. At the population level the overall prevalence rate for psychiatric disturbance was 21.8%, higher among boys (29.8%) than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 51 publications
5
31
2
Order By: Relevance
“…[1,7,18] No epidemiological studies on anxiety disorders among Finnish adolescents have been conducted. Almquist et al [19] reported a low estimate of 0.1% for SP among 8-9-year-old children, based on parental reports. One study [20] using the Schedules for Clinical Assessment in Neuropsychiatry (SCAN) interview [21] estimated a onemonth prevalence of 1.2% for SP among Finnish young adults aged 20-24 years.…”
Section: Introductionmentioning
confidence: 96%
“…[1,7,18] No epidemiological studies on anxiety disorders among Finnish adolescents have been conducted. Almquist et al [19] reported a low estimate of 0.1% for SP among 8-9-year-old children, based on parental reports. One study [20] using the Schedules for Clinical Assessment in Neuropsychiatry (SCAN) interview [21] estimated a onemonth prevalence of 1.2% for SP among Finnish young adults aged 20-24 years.…”
Section: Introductionmentioning
confidence: 96%
“…School-aged children's problems and needs for care are often manifested as behavioural and emotional disorders and may be related to problematic life situations (1)(2)(3)(4). In western countries, 15-22 % of school-aged children suffer from psychiatric disorders (2,3,(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…In western countries, 15-22 % of school-aged children suffer from psychiatric disorders (2,3,(5)(6)(7). A longitudinal epidemiological survey carried out in Germany focused on pupils aged 8 and 13.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations